Al-Ghazali's Epistemology in Islamic Religious Education: The Integration of Knowledge, Faith, and Morals - Bayu Mujrimin (DAAR EL-KAMIL: Multidisciplinary Journal, 2025)
This paper examines al-Ghazali’s epistemology in the context of Islamic religious education, focusing on the integration of knowledge, faith, and morality. Al-Ghazali views knowledge not merely as an intellectual tool but as a means to draw closer to God and purify the soul (tazkiyatun nafs). In this framework, knowledge must be accompanied by firm faith and noble character to avoid becoming unbeneficial knowledge. Contemporary Islamic education often emphasizes cognitive aspects while neglecting spiritual and moral dimensions. Through a library research approach, this article highlights the importance of integrating intellectual and spiritual elements in the teaching of Islamic Religious Education (PAI). Al-Ghazali’s thoughts offer a solution to the moral and spiritual crisis in education and encourage the development of a holistic and transformative Islamic education curriculum.